2022
DOI: 10.1111/jeu.12960
|View full text |Cite
|
Sign up to set email alerts
|

Molecular prevalence and subtypes distribution of Blastocystis sp. among outpatients and inpatients in north and south areas of Henan Province, China

Abstract: Blastocystis sp. is one of the most common intestinal parasites in humans and many animals. To further understand the infection of Blastocystis hominis (B. hominis) and the distribution of its genotype in some areas of Henan Province, China, 793 stool samples from outpatients and inpatients in Xinxiang City and Xinyang City, Henan Province were collected from April 2020 to July 2022. The samples were detected by polymerase chain reaction and analyzed by univariate analysis and logistic regression analysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The clinical samples used in this study were from Xinxiang City, China. It was reported that there were 8 subtypes (ST1-ST7, ST12) in the Chinese, and only ST1, ST3, ST4, ST6 and ST7 were reported in Xinxiang City ( Deng et al., 2019 ; Zhang et al., 2019 ; Mei et al., 2023a ). Although only ST3, ST4 and ST7 were included in the 56 clinical samples tested here, the results of RPA-LFD were completely consistent with those of cPCR, indicating that this method has good clinical application potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical samples used in this study were from Xinxiang City, China. It was reported that there were 8 subtypes (ST1-ST7, ST12) in the Chinese, and only ST1, ST3, ST4, ST6 and ST7 were reported in Xinxiang City ( Deng et al., 2019 ; Zhang et al., 2019 ; Mei et al., 2023a ). Although only ST3, ST4 and ST7 were included in the 56 clinical samples tested here, the results of RPA-LFD were completely consistent with those of cPCR, indicating that this method has good clinical application potential.…”
Section: Discussionmentioning
confidence: 99%
“…Blastocystis spp. is a common intestinal protozoan parasites found in humans and many animals ( Mei et al., 2022 ). The infection rate of Blastocystis spp.…”
Section: Introductionmentioning
confidence: 99%